The Nightingale Court Experiment: Lessons for Access to Justice in a Post-Pandemic World - Naidu, Natasha (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2023)
The literature is yet to consider the contribution of Nightingale Courts to access to justice in England and Wales during the COVID-19 pandemic. Nightingale Courts are courts that have been set up in repurposed buildings, such as town halls, hotels, and theatres, to facilitate socially distanced trials and hearings. I fill this gap by asking: to what extent have Nightingale Courts addressed access to justice concerns during the pandemic, and what lessons do Nightingale Courts hold for access to justice across jurisdictions and in the future? I argue that though costly and complex, Nightingale Courts have helped to prevent a further worsening of delay during the pandemic. Then, I explore the lessons of the Nightingale Court experiment for access to justice across jurisdictions and in a post-pandemic world. I consider Nightingale Courts as an experiment for legal architecture, informal justice, and adaptation and resilience. I conclude that Nightingale Courts have maintained and preserved access to the legal system during a time of crisis and thereby contributed to the resilience of the system.